The use of earthworm meal (Lumbricus rubellus) as anti-pullorum agent in feed additive of broiler chicken - Damayanti, Ema; Sofyan, Ahmad; Julendra, Hardi; Untari, Tri (Indonesian Journal of Animal and Veterinary Sciences, 2009)
The aim of this research was to study the use of earthworm meal (TCT) L. rubellus as anti pullorum agent in poultry feed additive (IP). The antibacterial activity of TCT against Salmonella pullorum was examined using diffusion agar method at each of the following concentrations: 0, 25, 50, 75 and 100% (w/v) in 100 ÂµL DMSO. In vivo test was conducted using 80 broiler chicken and were infected by S. pullorum with treatments of: IP0: IP contained 0% TCT, IP1: IP contained 25% TCT, IP2: IP contained 50% TCT, IP3: IP contained 75% TCT and IP4: IP contained 100% TCT. Each treatment was replicated 4 times with 4 chicks each. Feed additive was periodically fed to broiler during 7 days before and 10 days after infection. Anti-pullorum activities were evaluated using serology test, isolation and biochemical identification of S. pullorum. The results showed that 75% TCT was optimum to inhibit S. pullorum in vitro. The isolation and identification of S. pullorum results showed that 0 out of 8 (0%) broilers treated with IP4 was not infected by S. pullorum whereas 1 out of 2 (50%) broilers treated with IP0 were infected by S. pullorum. The reduction of S. pullorum prevalence as followed by increasing TCT in feed additive. In conclusion, TCT as poultry feed additive could inhibit S. pullorum infection. Key words: Earthworm Meal, Feed Additive, S. Pullorum